Chronic rhinosinusitis precipitated by tumor necrosis factor alpha inhibitors is the phenotype of chronic rhinosinusitis without nasal polyps. Issue 1 (3rd December 2019) - Papagiannopoulos, Peter; Devins, Kyle; Tong, Charles Ching Lick; Yver, Christina; Patel, Neil N.; Kuhar, Hannah N.; Bosso, John V.; Kohanski, Michael A.; Tajudeen, Bobby A.; Kuan, Edward C.; Batra, Pete S.; Cohen, Noam A.; et al.
Abstract : Background: Chronic rhinosinusitis (CRS) is a frequently observed condition in patients with immunodeficiency secondary to tumor necrosis factor alpha inhibitors (TNFαis). The histologic features of CRS caused by TNFαis have yet to be determined and may have important implications in understanding the pathophysiology of the disease process. Methods: A structured histopathology report was used to analyze sinus tissue removed during functional endoscopic sinus surgery (FESS). These structured histopathology variables were compared among patients with CRS on TNFαi (CRSαi), CRS without nasal polyps (CRSsNP) patients, and CRS with nasal polyps (CRSwNP) patients. Results: Eighteen CRSαi, 91 CRSwNP, and 113 CRSsNP patients undergoing FESS were analyzed. Compared to CRSsNP, CRSαi patients exhibited increased mucosal ulceration (16.7% vs 0.9%, p < 0.008), increased fibrosis (100% vs 34.5%, p < 0.001), and increased presence of Charcot‐Leiden crystals (16.7% vs 0%, p < 0.002). Compared to CRSwNP, CRSαi patients demonstrated increased fibrosis (100% vs 54.9%, p < 0.001), decreased presence of subepithelial edema (44.4% vs 69.2% p < 0.043), decreased eosinophil aggregates (22.2% vs 47.3% p < 0.042), and fewer eosinophils per high‐power field (44.4% vs 73.6%, p < 0.017). Conclusion: CRSαi exhibits structured histopathology more similar to CRSsNP. In the appropriate clinical context, it may be reasonable that the medical regimen for these patients be focused on a more antineutrophilic, macrolide‐based approach. This study provides insight into the inflammatory environment of patients with CRSαi and may have implications for disease management.